Cancer TARGETases: DSB repair as a pharmacological target - Samadder, Pounami; Aithal, Rakesh; Belan, Ondrej; Krejci, Lumir (Pharmacology & therapeutics, 2016)
Cancer is a disease attributed to the accumulation of DNA damages due to incapacitation of DNA repair pathways resulting in genomic instability and a mutator phenotype. Among the DNA lesions, double stranded breaks (DSBs) are the most toxic forms of DNA damage which may arise as a result of extrinsic DNA damaging agents or intrinsic replication stress in fast proliferating cancer cells. Accurate repair of DSBs is therefore paramount to the cell survival, and several classes of proteins such as kinases, nucleases, helicases or core recombinational proteins have pre-defined jobs in precise execution of DSB repair pathways. On one hand, the proper functioning of these proteins ensures maintenance of genomic stability in normal cells, and on the other hand results in resistance to various drugs employed in cancer therapy and therefore presents a suitable opportunity for therapeutic targeting. Higher relapse and resistance in cancer patients due to non-specific, cytotoxic therapies is an alarming situation and it is becoming more evident to employ personalized treatment based on the genetic landscape of the cancer cells. For the success of personalized treatment, it is of immense importance to identify more suitable targetable proteins in DSB repair pathways and also to explore new synthetic lethal interactions with these pathways. Here we review the various alternative approaches to target the various protein classes termed as cancer TARGETases in DSB repair pathway to obtain more beneficial and selective therapy.
Keywords: Molecular Targeted Therapy; cílená molekulární terapie; DNA Repair; oprava DNA; nádory; Animals; lidé; Neoplasms; dvouřetězcové zlomy DNA; DNA Breaks, Double-Stranded; Humans; zvířata